Study on the perspective of population control of capybaras (Hydrochoerus hydrochaeris) by reversible immunocontraceptive method - Rosenfield, Derek Andrew (2019)
In Brazil, the invasion of urban areas by capybaras (Hydrochoerus hydrochaeris) represents a severe public health problem because of their epidemiological importance as an amplifying host for Rickettsia, the causative agent of the tick-spread disease Brazilian Spotted Fever. This is in addition to the humancapybara conflicts (traffic accidents, agricultural damage, etc.). Capybaras resistance to adverse environmental conditions, high proliferative rates that are concurrent with reduction by natural predators, and laws against hunting mean that their population can quadruple in one year, consequently, increasing the beforementioned problems in anthropic areas. In this thesis, a population control model, based on immunocontraception, was used for the first time in H. hydrochaeris. The anti-GnRH vaccine (GonaCon), a single-dose recombinant, was administered intramuscularly, causing prolonged infertility in both sexes. To study the antifertility effects in this species, multidisciplinary studies were conducted; for a period of 36 months, 20 adult capybaras (10 males and 10 females); divided into two groups (control and treated) were investigated. Prior to the first intervention, animals were observed for reproductive behavior, fertility, and social group dynamics. Furthermore, positivereinforcement conditioning was used to facilitate physical and chemical restraint, minimizing capture-related stress. During the initial event, animals were health examined, ID marked, and biomaterials were collected, serving as a base-reference. Biomaterials were collected periodically (every 34 months), and investigations of contraceptive impacts on reproductive behavior and the group\'s integrity were carried out. Results showed: GonaCon-treated individuals ceased mating activity, with no direct births observed, confirmed by alterations to the reproductive physiology (spermatogenesis and folliculogenesis). Nevertheless, agonistic, courtship and alloparental behavior was preserved, maintaining the group\'s integrity. As a result, population growth was reduced, suggesting that immunization against GnRH is an effective long-term antifertility method in capybaras. Motivating critical discussions on non-lethal wildlife population control in Brazil, and the pressing issues on synanthropic species (capybaras), the study\'s intent was to provide an alternative strategy and, possibly, a national model to mitigate humanwildlife conflicts and zoonotic disease spread.